Nghiên cứu các yếu tố ảnh hưởng đến xây dựng thương hiệu cá nhân của sinh viên Đại học Bách khoa Hà Nội - Nguyễn Thị Oanh, Nguyễn Thị Oanh; Nguyễn Thị Thanh Thủy Nguyễn Thị Thanh Thủy (Tạp chí Giáo dục, 2026)
Personal branding has become increasingly essential for university students in the context of digital transformation and the growing demands of the labor market. This study examines the factors influencing personal branding behavior among students at Hanoi University of Science and Technology based on the ARCS (Attention, Relevance, Confidence, Satisfaction) motivational model through a quantitative survey of 624 students. Data were analyzed using reliability testing, descriptive statistics, correlation analysis, and multiple regression analysis. The results show that the level of participation in personal branding is moderately high, with intrinsic motivational factors having a stronger influence than extrinsic constraints. Attention, relevance, satisfaction, and career readiness have a positive impact on personal branding behavior, while confidence and socio-cultural barriers do not show a significant impact. The results also show that engineering students tend to prioritize professional competence over strategic selfexpression. The study proposes developing a personal branding measurement and evaluation framework that integrates academic profiles, digital identity management, learning engagement, and open educational resources to promote sustainable student development and inform higher education management activities.